MICROSCALE STUDY ON WATER INJECTION FLOW PATTERN IN FRACTURED HELE-SHAW CELL - ADRIANSAH, NUR FAZLINIZA (2021)
Flow pattern in the 2-phase fractured Hele Shaw cell during waterflooding affected by different parameters such as the injection rate and different fracture orientation.